Synthesis and Evaluation of Antioxidant Activity of Some New Heterocyclic Compounds Bearing the Benzo[B]Furan Moiety - Abdel-motaal, Marwa; Kandeel, E. M.; Abou-Elzahab, M.; Elghareeb, F. (European Scientific Journal, ESJ, 2017)
New compounds were synthesized by the reaction of 3-acetyl-5- methoxy-2-methylbenzofuran (1) with cyanoacetylhydrazine which afforded the hydrazide hydrazone derivative 2. Compound 2 underwent a series of heterocyclization reactions to give the new pyrazole, isoxazole, cyclopentanothiophene, thiazole, triazole, 2H-chromene and pyridone derivatives (3-13). The elemental and spectral data (IR, 1H NMR and MS) characterized their structures. Screening for some selected compounds was carried for their potential antioxidant activities using ABTS. Among the tested samples compounds 9, 11, 5 and 10 exhibited promising activity.